A nurse-led parental self-efficacy promotion program in parents of children with autism spectrum disorder: a quasi-experimental protocol - Dai, Yushen; Zou, E.; Ji, Yan; Chen, Xiuxian; Chen, Miaoying; Chen, Kaiyun; Huang, Baoqin; Xu, Min; Guo, Qiuling; Cai, Meiling; Deng, Tao; Wei, Yao; et al. (Frontiers in Psychiatry, 2025)
PurposeParents of children with autism spectrum disorder (ASD) often lack the knowledge and confidence to implement early intervention. This study will evaluate the effects of a parental self-efficacy promotion program on parenting self-efficacy, parenting stress, intervention compliance, and family quality of life for parents of children with ASD.Design and methodsThis two-arm, pretest, post-test quasi-experimental study recruits 80 parents in one tertiary hospital in China. The control group receives routine care, and the intervention group receives a 1-month self-efficacy promotion program on the basis of usual care. This program consists of one face-to-face session and three online sessions, supplemented by a written pamphlet. Content includes goal setting, experience sharing, verbal encouragement, and mobilizing of positive emotions.ConclusionThis study will empower the nurses as leaders to promote the well-being of parents of children with ASD and improve the early family intervention for their child by providing a parental self-efficacy promotion program.Practice implicationsParents need support to implement intervention in the family for their child with ASD. A nurse-led program targeted at improving parental self-efficacy is worth considering.